Young people, youth work & the 'levelling up' policy agenda. (February 2022) - Ord, Jon; Davies, Bernard
'Levelling UP' has taken on considerable significance in the policy discourses of the Johnson conservative government, particularly regarding the English regions. However, what is meant by Levelling up has been far from clear, although if it is to mean anything it must at least in part mean addressing the needs of disadvantaged and left behind communities. Key premises of this paper are that young people must be considered valued members of those communities; and that, to meet their expressed needs, youth work can be the best placed service for (re)investment, not least because it has demonstrated that it consistently enables a wide variety of outcomes in their lives. The investment required must be seen in the context of the huge austerity cuts to youth services in England which disproportionately affected disadvantaged communities. To make the case for 'levelling up' to completely rebuild as well as further develop those services. This paper brings together an analysis of past and current youth policies with a range of relevant empirical data.